Microstructure and microindentation of Ti3SiC2 – Titanium filler brazed joints by tungsten inert gas (TIG) process. Issue 9 (15th June 2017) - Hadji, Y.; Tricoteaux, A.; Ben Ghorbal, M.G.; Yahi, M.; Badji, R.; Sahraoui, T.; Hadji, M.; Barsoum, M.W.
Abstract: Herein we study the joining of Ti3 SiC2 - a MAX phase - with a Ti filler (Ti3 SiC2 /Ti-filler) using a TIG-brazing process. The microstructures of the interfaces were investigated by scanning electron microscopy and energy dispersive spectrometry. When Ti3 SiC2 comes into contact with the molten Ti - filler during the TIG-brazing operation, it starts decomposing into TiCx and a Si-rich liquid. Simultaneously, the molten Ti infiltrates into the Ti3 SiC2 resulting in a 200 µm thick duplex region, comprised of TiCx and a Ti-rich phase with some dissolved Si. Both Si and C are found in the solidified Ti; the Si source is from the Si-rich liquid, while the presence of C indicates that some of the C diffused into the Ti. Upon cooling, C- containing Ti- rich lamellae form the solidified Ti. Microindentation results of the decomposed Ti3 SiC2 layer show an increase in hardness and a decrease in elastic modulus relative to T3 SiC2 . Notably, no cracks were observed.